A ideia principal de um texto acadêmico: um meio para descrever tendências semânticas - Sanoki, Koichi (2019)
This thesis describes how to formulate questions of the paradoxical type in semantic words about the main idea of an academic article, arousing curiosity to perform the reading Complete of such an article. By locating this main idea of a text that is on a digital media, an algorithm described to interpret it with an object-oriented structural technique is applied. The primary function of this algorithm is to rearrange the parts of the text to make sense As a computational object that contains the main idea. The process of locating the Idea begins with searches in virtual libraries, journal repositories, or other Publications where part of the theme has already been carried on a computational media with the Its bibliog raphical references. To support this function, there is the identification of the Subheadings and large items found in the text, such as introduction, methodology, Discussion, outcome, and conclusion, and the production of a parallel between the theme of this article and an object in real life, between the descriptions of the introduction and characteristics of the object, and between the methodologies described and the class methods in structure oriented to objects. With the items identified, the next step is the detection of grammatical periods and the verification of which are the types of verbs, because they describe the actions, or static of the sentence, which is the object of this thesis. Being the text, with semantic value, a seam and an interweaving of words resulting in a message of information that at first do not obey the rules of academic composition, neither the logical sequences, nor the types of heuristic algorithms, becomes A standardized sequence is required in the descriptions of the theme characteristics. When the organization is organized, a standardization is created according to what the algorithm determines, so that the article is treated as an object-oriented structure. This is the way to organize what actions and functions The article describes, and which will be rewritten in the computational schema as: Object, property, and functions. Once the idea is identified, questions will be generated with characteristics of the paradoxal type, such as: ”Exit right” and ”enter from the left”, and with semantic characteristics, such as: ”See” is the act of seeing, ”assembling” is to be on, affirmations that generate Polemic inquiries for those who do not see, or for those who cannot get around, and that may awaken in the researcher the interest in reading a certain academic text, which will then question what is the idea that these words associated with semantic values represent in this article. The questions are related to the words that compose the main idea and the secondary ideas found in the grammatical periods of the text. The formula of the question about the main idea is to have the interrogative pronoun questioning the semantic value of the words in paradoxical type, supported by the computational algorithm that identifies the main item and the secondary items of an academic article, and generates Characteristics with a type of irony that the original text does not explicitly describe. With such identity arises the curiosity that makes necessary the complete reading of the text, and the acceptance, or not, of the forms of inquiries described by this thesis